Consequences of the Commoditization of Nature by Tourism - Cantú Martínez, Pedro César (2022)
The present manuscript shows how the commodification of nature according to the vision of neoliberal development has outlined a vision of appropriation where tourism activity is importantly located. In this event, the prevailing tourism development models have promoted being generators of local development, as a meeting point for cultural exchanges and beautification of the sites where they are established. Thus, through an argumentative and documentary research for the contrast of theoretical and empirical reality, the commodification of nature by tourism is analyzed, and this appreciation is deliberated. The results of the evaluation carried out show that social inequality, acculturation, environmental pollution, and deterioration of the natural environment are being generated in these spaces. In such a way, the economic component of tourism as a factor raises and gravitates in the social and environmental imbalances that are caused in the natural environment, even though it is named as sustainable tourism.